1982
DOI: 10.3168/jds.s0022-0302(82)82376-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Heat and Cold Stressors on Plasma Immunoglobulin and Mitogen-Induced Blastogenesis in Calves

Abstract: Fifty-six Holstein calves were used to investigate effects of heat and cold stressors on mitogen-induced blastogenesis of isolated peripheral blood mononuclear cells and immunoglobulins G1 and M in blood plasma. Calves were exposed to constant hot (35 degrees C), constant cold (-5 degrees C), or thermoneutral (23 degrees C) ambient conditions in environmentally-controlled chambers. Immune responses were measured soon after introduction into environmental chambers (3 days) and after various degrees of adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 33 publications
1
23
1
Order By: Relevance
“…The eosinophile percentage of heat-stressed calves was reduced to half of the control level, although this trend was not statistically significant (K ELLEY et al, 1982). In another study, steers implanted with Zeranol and exposed to a cold stress exhibited such a decrease, which shows that implantation did not counteract the effect of stress on their hematological values (K EL i.EY et al, 1981).…”
Section: Discussionmentioning
confidence: 94%
“…The eosinophile percentage of heat-stressed calves was reduced to half of the control level, although this trend was not statistically significant (K ELLEY et al, 1982). In another study, steers implanted with Zeranol and exposed to a cold stress exhibited such a decrease, which shows that implantation did not counteract the effect of stress on their hematological values (K EL i.EY et al, 1981).…”
Section: Discussionmentioning
confidence: 94%
“…In dairy cows it has been shown to reduce migration of leucocytes to the udder in response to chemotactic stimuli (Elvinger et al 1992). In the month-old calf it reduced plasma lgGi levels by 25% and increased the circulating levels of a factor which potentiates mitogenesis in monocytes (Kelley et al 1982). The latter effect did not occur in a comparable study in lambs (Minton & Blecha 1990), but heat stress has been shown to suppress T-cell-mediated immune responses in sheep, and this effect did not appear to be mediated by adrenocorticosteroids (Niwano et al 1990).…”
Section: Heat Stress and Shadementioning
confidence: 92%
“…Working with calves, Kelley et al (1982a) concluded that heat stress is responsible for alterations of the immune response and that the heat-stress-induced changes in immune events depend on the type of immune response and the length of time that calves are exposed to the stressor. In another study, also undertaken with calves, the same authors (Kelley et al 1982b) found that heat stress had no direct effects on the proliferation of mitogen-stimulated peripheral blood mononuclear cells (PBMC). Furthermore, two in vitro studies demonstrated that exposure of bovine lymphocytes to short and severe heat shock reduced their responsiveness to mitogens or decreased the number of viable cells (Elvinger et al 1991;Kamwanja et al 1994).…”
Section: Introductionmentioning
confidence: 92%